Analisis Efektivitas Surat Edaran Mahkamah Agung Nomor 4 Tahun 2014 pada Rumusan Hukum Hasil Rapat Pleno Kamar Peradilan Agama terhadap Konsistensi Putusan Cearai di Pengadilan Agama Medan: Studi Kasus Tahun 2023-2024 - Tuseno, Tuseno; Siregar, Ramadhan Syahmedi (RIO LAW JURNAL, 2024)
The purpose of marriage is to obtain happiness for the married couple. However, it is not uncommon for both of them to feel that after marriage they have not achieved happiness, the goal of the marriage itself has not been achieved. Because the goal of marriage has not been achieved, the right solution is divorce. In order for a marriage to be divorced by the court, it must be proven that the reasons for divorce have been met because if there are no reasons for divorce, the judge will reject the divorce petition so that legally a marriage that does not achieve happiness cannot be divorced. After conducting an analysis of the Medan religious court decision and Supreme Court Circular Letter Number 04 of 2014, it was found that the existence of SEMA has proven effective in filling the legal vacuum. The judge at the Medan Religious Court can interpret the occurrence of a quarrel between husband and wife by looking at the fact that there was a separation between husband and wife. Because indeed, if the reason is that they have separated, the judge is constrained by the rule which requires it to last for 2 (two) consecutive years so that the existence of SEMA Number 04 of 2014 which allows deciding on a divorce even though they have not been separated for 2 (two) years makes it easier for judges to decide on a divorce where they have already been separated. It is proven that from 2023 to May 2024, Medan Religious Court judges have decided on divorce in 4,076 cases.